(untitled) (Revista Direito em Debate, 2020)
Using Heidegger as a theoretical framework, the paper aims to observe the issue of the right to housing in the light of constitutionalism. The shortage of the realization of human rights in late modern countries such as Brazil, especially those in which the event of contemporary constitutionalism sets in relatively success becomes a problem that goes beyond the political, administrative and legal issues, touching, first of all, in hermeneutic issue. Before intent the realization of the new, it must be understood to its full extent so that the questions concerning them have adequate answers. If modern normativist positivism offers insufficient, contradictory and precarious answers, must be sought the meaning of things in them and in their globality, the only acceptable reference for the understanding of ones to arrive at adequate answers. From the theoretical ground that gives rise to the new legal dimensions of housing (more complex than the simple housing) to its constitutionally adequate understanding and application there is a long hermeneutic path that will be addressed in this article.